2017
DOI: 10.1097/jac.0000000000000189
|View full text |Cite
|
Sign up to set email alerts
|

Brazil's National Program for Improving Primary Care Access and Quality (PMAQ)

Abstract: Despite some remarkable achievements, there are several challenges facing Brazil's Family Health Strategy (FHS), including expanding access to primary care and improving its quality. These concerns motivated the development of the National Program for Improving Primary Care Access and Quality (PMAQ). Although voluntary, the program now includes nearly 39 000 FHS teams in the country and has led to a near doubling of the federal investment in primary care in its first 2 rounds. In this article, we introduce the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
14

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(64 citation statements)
references
References 24 publications
0
50
0
14
Order By: Relevance
“…Some schemes rewarded just a handful of indicators, for instance a P4P scheme in Haut-Katang in the DRC rewarded seven indicators [45] or a P4P scheme in Haiti rewarded 14 indicators [46]. However, others are extremely complex, a good example is Brazil's national P4P scheme (called PMAQ -National Program for Improving Primary Care Access and Quality), which rewarded over 600 different indicators [47]. Often studies only reported a sub-set of incentivised indicators (for instance, those that are being measured or assessed within the study) and do not make it clear which other indicators are incentivised by the programme.…”
Section: Design Of P4p Schemes In Lmicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some schemes rewarded just a handful of indicators, for instance a P4P scheme in Haut-Katang in the DRC rewarded seven indicators [45] or a P4P scheme in Haiti rewarded 14 indicators [46]. However, others are extremely complex, a good example is Brazil's national P4P scheme (called PMAQ -National Program for Improving Primary Care Access and Quality), which rewarded over 600 different indicators [47]. Often studies only reported a sub-set of incentivised indicators (for instance, those that are being measured or assessed within the study) and do not make it clear which other indicators are incentivised by the programme.…”
Section: Design Of P4p Schemes In Lmicsmentioning
confidence: 99%
“…It was not uncommon for schemes to measure the performance of one actor and provide payment to another actor. For instance, Brazil's national P4P scheme measured the performance of primary healthcare facilities but paid municipal health managers [47].…”
Section: Who Is Incentivised?mentioning
confidence: 99%
“…According to Macinko et al 4 , PMAQ-AB can be considered as one of the largest global initiatives to improve the performance of Primary Care and it has led to double the federal investments in the area. According to the authors, the data generated are beginning to be used to understand the structural and operational constraints faced by health professionals.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike other countries engaging in P4P schemes, the Ministry of Health is not involved directly in these payments, instead municipal managers have the autonomy to choose whether to use P4P with participating teams from municipalities or simply to use the payments for primary care actions. Studies reveal that 39 000 Family Health Strategy teams participate in PMAQ and are located throughout the country (Macinko, Harris and Rocha, 2017 [4]).…”
Section: Application Of Pay-for-performance Schemesmentioning
confidence: 99%
“…Additional published research from Brazil shows that P4P has resulted in changes in the management regarding the work process of these teams. Since its debut, "PMAQ has led to an increase in federal investment for infrastructure and performance incentives in primary care from BRL 770 million in 2011/12 to BRL 4.2 billion (about USD 1.2 billion) in 2014/15" (Macinko, Harris and Rocha, 2017 [5]). These studies also argued that P4P has had an inductive role in increasing the quality and access of primary care services offered by teams participating in P4P programmes.…”
Section: Application Of Pay-for-performance Schemesmentioning
confidence: 99%